Development of Augmented Reality Learning Media Based on Inquiry Based Learning Using Assemblr Edu on Light and Properties Material - Sudarno, Nida Listiani; Anggoro, Subuh; Fukui , Masanori (Journal of Educational Sciences, 2025)
This study aims to develop Augmented Reality (AR)-based learning media using an Inquiry-Based Learning (IBL) approach through the Assemblr Edu platform, focusing on light and its properties for fifth-grade elementary students. The background of this research lies in the low conceptual understanding of students due to the limited use of interactive and contextual learning media. The research used a Research and Development (R&D) method adapted from the 4D model, involving needs analysis, media design, expert validation, product trials, and dissemination. Data were collected through interviews, questionnaires, and documentation, and analyzed qualitatively and quantitatively. Validation results from material experts (94.28%) and media experts (82.66%) indicated that the media was “highly feasible.” Small-scale trials involving 11 students showed a high interest rate (93.93%), demonstrating that AR media significantly enhanced students’ engagement and understanding of abstract concepts such as reflection, refraction, and light transmission. The findings conclude that AR-based learning media with an IBL approach is effective in improving students’ comprehension and motivation, offering an innovative solution to enhance the quality of science learning in the digital era.